2022
DOI: 10.1002/cpz1.456
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Fate Mapping

Abstract: Tissue‐resident macrophages are present in all tissues where they perform homeostatic and immune surveillance functions. In many tissues, resident macrophages develop from embryonic progenitors, which mature into a self‐maintaining population through local proliferation. However, tissue‐resident macrophages can be supported by recruited monocyte‐derived macrophages during scenarios such as tissue growth, infection, or sterile inflammation. Circulating blood monocytes arise from hematopoietic stem cell progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…Thus, we utilized the CCR2 CreER R26 Tdtomato mouse, which allows for specific labeling of individual waves of blood monocytes following tamoxifen treatment, enabling tracking of their differentiation upon entry into tissue. 31 33 Tamoxifen treatment of CCR2 CreER R26 Tdtomato mice revealed robust classical monocyte labeling in the blood, but no labeling of pancreatic tissue-resident macrophages ( Figures S1A – S1D ), consistent with a reported lack of Ccr2. 34 To track monocyte differentiation in PDA in the presence of tumor-specific T cells, we orthotopically implanted KPC2a tumor cells that express a model neoantigen click beetle red luciferase (CB) 30 into the pancreas of CCR2 CreER R26 Tdtomato mice following a single dose of tamoxifen ( Figure 1A ).…”
Section: Resultssupporting
confidence: 65%
“…Thus, we utilized the CCR2 CreER R26 Tdtomato mouse, which allows for specific labeling of individual waves of blood monocytes following tamoxifen treatment, enabling tracking of their differentiation upon entry into tissue. 31 33 Tamoxifen treatment of CCR2 CreER R26 Tdtomato mice revealed robust classical monocyte labeling in the blood, but no labeling of pancreatic tissue-resident macrophages ( Figures S1A – S1D ), consistent with a reported lack of Ccr2. 34 To track monocyte differentiation in PDA in the presence of tumor-specific T cells, we orthotopically implanted KPC2a tumor cells that express a model neoantigen click beetle red luciferase (CB) 30 into the pancreas of CCR2 CreER R26 Tdtomato mice following a single dose of tamoxifen ( Figure 1A ).…”
Section: Resultssupporting
confidence: 65%
“…Acute cold challenge: All CCR2 creER/+ R26 TdTomato mice were given 200 µL 20 mg/mL tamoxifen (TAM, MilliporeSigma #T5648) in corn oil (MilliporeSigma #C8267) through oral gavage (82,83).…”
Section: Monocyte Fate Mappingmentioning
confidence: 99%
“… 126 , 127 Contrary to the traditional view that all tissue macrophages are derived from circulating monocytes, recent fate mapping studies have revealed that many TrMΦ are established during embryonic development and maintain themselves through local proliferation, independent of adult monocyte input. 128 , 129 For example, microglia, the resident macrophages of the central nervous system, have been shown to originate from yolk sac‐derived progenitors that seed the brain early in embryonic development. 130 Similarly, Kupffer cells, the resident macrophages of the liver, are derived from a combination of yolk sac and fetal liver progenitors.…”
Section: Macrophage Plasticity: From Historical Origins To Contempora...mentioning
confidence: 99%